2010
DOI: 10.1016/j.joca.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early changes in the articular cartilage transcriptisome in the rat meniscal tear model of osteoarthritis: pathway comparisons with the rat anterior cruciate transection model and with human osteoarthritic cartilage

Abstract: We identified a large number of differentially expressed genes in the articular cartilage of the MT model. While there was lack of overall identity in cartilage gene expression between the rat models and human OA, several key biological processes were recapitulated in the rat MT OA model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 29 publications
4
69
0
Order By: Relevance
“…Recent studies address how inflammatory gene expression varies with time after injury in common rodent models. Wei and colleagues [31] compared cartilage transcriptomic profiles in rats undergoing meniscal transection to sham-operated controls at days 3, 7 and 21 post-injury. 337 differentially expressed genes were observed at day 3, with smaller numbers at day 7 (79) and day 21 (112).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies address how inflammatory gene expression varies with time after injury in common rodent models. Wei and colleagues [31] compared cartilage transcriptomic profiles in rats undergoing meniscal transection to sham-operated controls at days 3, 7 and 21 post-injury. 337 differentially expressed genes were observed at day 3, with smaller numbers at day 7 (79) and day 21 (112).…”
Section: Methodsmentioning
confidence: 99%
“…Many of these studies have focused on a single tissue, like articular cartilage 3, 4 , subchondral bone 5 or synovium 6, 7 most often at single time points. While these approaches have identified many novel genes with altered expression in OA, there is no information on how the gene product interactions may be altered to influence the development of the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, through the combination of good seed cell and gene engineering technology, the transfected cells were injected into the knee joint cavity. This strengthens target growth factor expression in cells, and the concentration reached a stable value [37]. And finally, the observation in cartilage repair effect was accomplished.…”
Section: Discussionmentioning
confidence: 77%
“…Also, in vivo experimental studies showed that TGF-β in chondrocytes mediates Smad2/3 signal through classical type I receptor ALK5, as well as Smad1/5/8 pathway through ALK1 receptor [35]. With the growth of age, the decrement of ALK5 was much faster as compared with ALK1, resulting in the differentiation of chondrocytes into the hypertrophic phenotype of osteoarthritis [36][37][38]. These studies might indicate that the decrease in ALK5/ALK1 ratio had broken the signal balance of TGF-β, so TGF-β signal was biased toward Smad1/5/8 signaling pathway, which made chondrocyte terminal differentiation and aggravated the process of cartilage arthritis.…”
Section: Discussionmentioning
confidence: 99%